Artificial prosthesis material based on polyvinyl alcohol / bacterial cellulose as well as preparation and application of artificial prosthesis material
Porous composite materials were prepared by foaming under surfactant conditions and cross-linking polyvinyl alcohol and bacterial cellulose by freeze-thawing method, which solved the problem of insufficient flexibility and biocompatibility of existing auricle prosthesis materials. A combination of high mechanical properties and good biocompatibility is achieved.
Patent Information
- Application Number
- CN202411167411.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-17
AI Technical Summary
The existing auricle prosthetic materials lack flexibility and elasticity, and the composite technology has problems such as long impregnation method and toxic side effects of chemical crosslinking agents, which fail to effectively improve the mechanical properties and biocompatibility of the materials.
Polyvinyl alcohol and bacterial cellulose are foamed under surfactant conditions and physically cross-linked by freeze-thawing method to prepare porous polyvinyl alcohol/bacterial cellulose composite materials to improve their mechanical properties and biocompatibility. .
The obtained materials have excellent mechanical properties, good biocompatibility and histocompatibility, and are suitable for plastic surgery and repair of artificial auricles and other parts. The preparation method is simple and efficient, environmentally friendly and non-toxic.
Smart Images

Figure CN119139550A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedicine, and particularly relates to an artificial prosthesis material based on polyvinyl alcohol / bacterial cellulose and a preparation method and application thereof. Background Art
[0002] The elastic cartilage of the auricle lacks the support of blood vessels, lymph and nerves, and its anatomical structure is delicate and complex. Once the defect is damaged, it is difficult to repair and reconstruct itself. The only treatment method is prosthesis transplantation. However, the costal cartilage ear reconstruction operation period is long, the carving is difficult, the trauma is large, and there are many complications in the donor site; the tissue engineering auricle scaffold often lacks sufficient mechanical strength; the biomaterial auricle reconstruction can avoid the above problems, and has a wide source and strong plasticity. The commonly used prosthetic material in clinical practice, high-density polyethylene (Medpor, Porex Corp, USA), has a hard texture, lacks flexibility and elasticity, and is easy to cause the scaffold to be squeezed and exposed. In addition, studies on silicone, polytetrafluoroethylene, polylactic acid and polyethylene glycol acid have shown that the material has insufficient adhesion to the tissue and causes inflammation. Therefore, an ideal auricle substitute that can match the mechanical and biological properties of human auricle tissue has not been found so far.
[0003] Bacterial cellulose, also known as bacterial nanocellulose (BNC), is a natural nanofiber hydrogel produced by microorganisms such as Bacillus oxykogata at the air-liquid interface. It has a unique three-dimensional nanofiber network structure, similar to the structure of the extracellular matrix, and has excellent mechanical properties such as good biocompatibility and flexibility. Studies have shown that bacterial cellulose is suitable as an implant material for ear cartilage replacement. However, its rigid nanofibers lack elasticity, which limits its application in the field of elastic cartilage materials. Polyvinyl alcohol (PVA) can form a hydrogel with a porous honeycomb network structure inside, which has good biocompatibility and excellent elasticity. It can provide elastic recovery and viscoelastic energy dissipation, which is similar to the physicochemical properties of elastic cartilage. However, when polyvinyl alcohol hydrogel is used alone as a cartilage replacement material, it cannot meet the requirements of its biological activity and mechanical strength. In addition, the network pores of natural BNC membranes and PVA hydrogels are small, which is not conducive to the growth, infiltration and extension of cells and tissues into the interior.
[0004] The existing technologies for composite modification of polyvinyl alcohol and bacterial cellulose are mostly impregnation or cross-linking. The impregnation method is time-consuming and has a low loading rate. The chemical cross-linking agent used in the cross-linking method often brings toxic side effects. In the field of artificial auricle, there has been no similar research report on the composite of homogenized bacterial cellulose and polyvinyl alcohol. Existing studies have mainly focused on bacterial cellulose membrane as the base material, and composited with polyvinyl alcohol by impregnation or chemical cross-linking. However, this method limits the composite amount of polyvinyl alcohol, and the cross-linking agent may also bring toxicity, and fails to significantly improve the elasticity of the material. The mechanical properties and biocompatibility of polyvinyl alcohol / bacterial cellulose composites prepared by freeze-thaw method have not been studied, nor have they been developed as plastic prosthetic materials such as artificial auricles. Summary of the invention
[0005] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide an artificial prosthesis material based on polyvinyl alcohol / bacterial cellulose and its preparation and application.
[0006] The invention provides a prosthetic material. The prosthetic material is obtained by foaming raw materials containing bacterial cellulose and polypropylene alcohol under surfactant conditions and combining a freeze-thaw method.
[0007] The present invention provides a method for preparing a prosthetic material, comprising:
[0008] (1) homogenizing the bacterial cellulose to break it into a homogenate, and collecting it by centrifugation to obtain a bacterial cellulose precipitate;
[0009] (2) mixing the polyvinyl alcohol aqueous solution, bacterial cellulose precipitate, and surfactant, stirring and foaming, freeze-thaw treatment, and washing to obtain a prosthetic material;
[0010] Alternatively, the polyvinyl alcohol aqueous solution and bacterial cellulose precipitate are mixed, stirred, freeze-thawed, and washed to obtain the prosthetic material.
[0011] In step (1), the bacterial cellulose slurry is homogenized by a homogenizer, and then the bacterial cellulose BNC precipitate is collected by centrifugation.
[0012] Preferably, the bacterial cellulose in step (1) is purified bacterial cellulose.
[0013] Preferably, the homogenization treatment parameters in step (1) are: 8000-12000 rpm, 15-30 min, and 3-5 times; the centrifugation is 5000-11000 rpm for 5-10 min.
[0014] In step (2), the polyvinyl alcohol aqueous solution is mixed with the bacterial cellulose precipitate, and a surfactant is added to stir and foam, and the two are physically cross-linked by freeze-thaw method to prepare a polyvinyl alcohol / bacterial cellulose composite material, and finally the material is repeatedly shaken and washed to obtain a prosthetic material.
[0015] In the step (2), the degree of polymerization of the polyvinyl alcohol is 400-2500, and the degree of alcoholysis is 50-99%.
[0016] The polyvinyl alcohol models in the step (2) are: polyvinyl alcohol 588 (degree of polymerization 500, degree of alcoholysis 88%, Shanghai Yuanye Biotechnology Co., Ltd.), polyvinyl alcohol 2088 (degree of polymerization 2000, degree of alcoholysis 88%, Shanghai Bid Pharmaceutical Technology Co., Ltd.), polyvinyl alcohol 2488 (degree of polymerization 2400, degree of alcoholysis 88%, Shanghai Bid Pharmaceutical Technology Co., Ltd.), polyvinyl alcohol 1799 (degree of polymerization 1700, degree of alcoholysis 99%, Shanghai Aladdin Biochemical Technology Co., Ltd.), polyvinyl alcohol 1750 (degree of polymerization 1700, degree of alcoholysis 50%, Sinopharm Chemical Reagent Co., Ltd.).
[0017] Preferably, the model of the polyvinyl alcohol is polyvinyl alcohol 1750 (polymerization degree 1700, alcoholysis degree 50%).
[0018] Preferably, the concentration of the polyvinyl alcohol aqueous solution in step (2) is 5-30% (w / v, g / mL);
[0019] Preferably, the polyvinyl alcohol aqueous solution is prepared by mixing polyvinyl alcohol and water and dissolving them at 90-100° C. to obtain the polyvinyl alcohol aqueous solution.
[0020] Preferably, the content of bacterial cellulose precipitation in the mixed system in step (2) is 10-40% (w / v, g / mL); the content of the surfactant is 0-3% (w / v, g / mL), and further preferably, the content of the surfactant is 1-3% (w / v, g / mL).
[0021] Preferably, the surfactant in step (2) is one or more of polyethylene glycol octylphenyl ether, sodium dodecyl sulfonate, sodium dodecyl sulfate, and fatty acids. The surfactant is used as a foaming agent to form pores.
[0022] More preferably, the surfactant is polyethylene glycol octylphenyl ether.
[0023] Preferably, the freeze-thaw treatment in step (2) is: thawing followed by freezing, wherein the freezing temperature is -80°C to -20°C, and the time is 12-48 hours; the thawing temperature is -4°C to room temperature, and the time is 8-12 hours; and the freeze-thaw treatment is cycled 1-5 times.
[0024] Furthermore, the thawing temperature is -4°C or room temperature, and the thawing time is 12 hours.
[0025] Preferably, in step (2), stirring is performed at 300-350 rpm for 5-15 min; and washing is performed by oscillation washing, wherein the time is 1-2 d and the rotation speed is 50-150 rpm.
[0026] The present invention provides an application of the prosthetic material in the field of cosmetic repair prosthetic materials for artificial auricle, cartilage, artificial skin, leather, chest, nose wing and mandible.
[0027] The present invention provides a prosthetic material (such as an artificial auricle) based on polyvinyl alcohol / bacterial cellulose, wherein the bacterial cellulose is homogenized and mixed with a polyvinyl alcohol solution and a surfactant (such as polyethylene glycol octylphenyl ether, etc.), and a freeze-thaw method combined with a surfactant foaming method is used for compounding and pore making, and finally the composite material is repeatedly oscillated and rinsed to obtain a porous polyvinyl alcohol / bacterial cellulose prosthetic material (such as an artificial auricle, etc.). Compared with a single hydrogel, the present invention uses a physical freeze-thaw method to make polyvinyl alcohol and bacterial cellulose interact through phase separation and hydrogen bonds, synergistically reshape the internal network structure of the material, obtain a porous structure, and make the composite material simultaneously exhibit unique elasticity and excellent physical and chemical properties, including high water content, high crystallinity, high mechanical strength and good biocompatibility, etc., and have better tissue compatibility and biomechanical properties matching human tissues than commercially available products (such as Medpor). The prosthesis preparation method is simple, efficient, and repeatable, and the prepared auricle replacement material has excellent mechanical properties and good biocompatibility, etc., and has great application potential in the field of artificial organs and plastic surgery repair.
[0028] Beneficial Effects
[0029] (1) The polyvinyl alcohol / bacterial nanocellulose porous composite material prepared by the present invention has excellent mechanical properties, unique honeycomb network pore structure and good biocompatibility, and other physical and chemical properties similar to those of the extracellular matrix, and can be used as a prosthetic material such as an auricle substitute for in vivo transplantation.
[0030] (2) The polyvinyl alcohol / bacterial nanocellulose porous composite material prepared by the present invention is not easily deformed, degraded or absorbed, is non-toxic and harmless, and is a new type of prosthetic material formed by natural hydrogel and polymer hydrogel.
[0031] (3) The present invention can effectively adjust the mechanical properties and network pore structure of the polyvinyl alcohol / bacterial nanocellulose material through the freeze-thaw cycle method and the surfactant pore-making method. The preparation is environmentally friendly, simple, and highly repeatable. The obtained polyvinyl alcohol / bacterial nanocellulose porous composite material has the potential to be used as a cosmetic repair prosthesis material for artificial auricle, cartilage, artificial skin, and chest, nose, jaw, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The compressive mechanical properties of polyvinyl alcohol / bacterial nanocellulose (PVA / BNC, PB for short) samples with different polyvinyl alcohol concentrations (8%, 12%, 16%, 20%) after 1-3 cycles of freeze-thaw: (A) is the compressive strength, and (B) is the compression modulus.
[0033] Figure 2 (Examples 1 and 2, Comparative Examples 1 and 2) are morphological structure diagrams of materials such as porous polyvinyl alcohol / bacterial nanocellulose (Porous PVA / BNC, abbreviated as PPB): wherein (A) is the macroscopic morphology of the material, (B) is the auricle-shaped PPB sample, and (C) is the microscopic morphology of the material.
[0034] Figure 3 (Examples 1 and 2, Comparative Examples 1 and 2) are infrared spectra of materials such as bacterial cellulose, porous polyvinyl alcohol / bacterial nanocellulose, etc.
[0035] Figure 4 (Examples 1, 2, Comparative Examples 1, 2) are the water properties of the materials: wherein (A) is the water content and (B) is the saturated swelling ratio. Figure 5 (Example 1) is a diagram of the compressive mechanical properties of materials such as 16% PPB, wherein (A) is the compressive strength, (B) is the compression modulus, (C) is the stress-strain curve of compression, (D) is the stress-strain curve of cyclic compression of PPB material, and (E) is the cyclic compression energy dissipation and loss coefficient of PPB material.
[0036] Figure 6 (Examples 1, 2, Comparative Examples 1, 2) are tensile mechanical property diagrams of materials such as PPB: wherein (A) is a tensile stress-strain curve diagram, (B) is elongation at break, (C) is tensile strength, and (D) is tensile modulus.
[0037] Figure 7 (Examples 1 and 2, Comparative Examples 1 and 2) are the suture strength of the material.
[0038] Figure 8(Examples 1 and 2, Comparative Examples 1 and 2) are the cell compatibility of the materials: wherein (A) is the CCK-8 absorbance value of the extract, (B) is the cell survival rate, (C) is the calcein staining micrograph, and (D) is the microscopic morphology of cells grown on the material surface for 1, 3, and 5 days.
[0039] Fig. 9 (Examples 1 and 2, Comparative Examples 1 and 2) are the results of hematoxylin-eosin staining (H&E) after the materials were subcutaneously embedded in rats for 7 days and 28 days.
[0040] Fig.10 (Examples 1 and 2, Comparative Examples 1 and 2) are the Masson staining results after the materials were subcutaneously embedded in rats for 7 days and 28 days.
[0041] Fig.11 The invention relates to a method for preparing a polyvinyl alcohol / bacterial cellulose porous composite material. DETAILED DESCRIPTION
[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0043] Related tests:
[0044] a. Morphology: Take a macroscopic photo of the material. Freeze-dry the sample for 72 hours after pretreatment. After gold coating, use a scanning electron microscope to observe the microscopic morphology of the material, using 5μm and 2μm scales.
[0045] b. Structural properties: Weigh the freeze-dried sample and measure the volume to calculate the bulk density (Apparentdensity, denoted as Ad) of the material, use a true density tester to test the skeleton density (Skeletaldensity, denoted as Sd) of the material, and calculate the porosity (Porosity) of the material according to the following formula. At the same time, use a fully automatic nitrogen adsorption specific surface area and porosity analyzer to test the specific surface area (Specific surface area) of the material.
[0046] Porosity (%) = (1 – Ad / Sd) × 100%
[0047] c. Fourier transform infrared spectroscopy: After freeze-drying the sample, total reflection Fourier transform infrared spectrometer was used to analyze the chemical structure of the sample surface.
[0048] d. Moisture content, water absorption and saturated swelling rate: Cut the samples into cylindrical shapes with a thickness of 5 mm and a diameter of 15 mm. Weigh the initial wet weight of the sample at room temperature, recorded as Wwet. Then freeze-dry and weigh, recorded as Wdry. Soak the sample in ultrapure water, and after a certain interval (5, 15, 30, 60, 120, 240, 480 min), remove the surface moisture of the sample and weigh it, recorded as Wt. The maximum water absorption rate is calculated as the saturated swelling rate, and the moisture content and water absorption rate of the sample are calculated by the following formula:
[0049] Moisture content (%) = (Wwet-Wdry) / Wwet×100%
[0050] Water absorption (%) = (Wt-Wdry) / Wdry×100%
[0051] e. Crystallinity: After freeze-drying, the crystallinity of the sample was tested using an X-ray diffractometer.
[0052] f. Compression mechanical properties: The compression and tensile mechanical properties of the samples were tested using a universal material testing machine, and a 1000N sensor was used. The samples were cut into cylindrical shapes of the same size (12mm in diameter and 5mm in thickness), and the samples were compressed at a speed of 5mm / min until the strain was 70% and then automatically returned to the initial position. The data obtained from the sensor were used to calculate physical quantities such as compression strength and compression modulus, and statistical graphs related to compression mechanics were drawn.
[0053] The loading and unloading speeds of the cyclic compression were set to 5 mm / min. After compression to 30% strain, the sample automatically returned to the initial position. After each cycle, the sample relaxed for 10 seconds. The energy dissipation capacity of the sample was tested by 20 cycles of compression. The stress-strain curve was drawn from the 1st, 5th, 10th, 15th, and 20th compression cycle data, and the energy dissipation and energy loss coefficient were calculated.
[0054] g. Tensile mechanical properties: Cut the samples into strips of the same size (30mm long, 10mm wide) with a gauge length of 15mm, stretch the samples at a speed of 50mm / min until they are completely broken, and then automatically return to their original position. Calculate the tensile strength, tensile modulus and elongation at break using the data obtained from the sensor, and draw statistical graphs related to tensile mechanics.
[0055] h. Suture strength: The test method of suture strength is similar to the tensile test. First, prepare a sample (30mm long, 10mm wide, 2.33±0.21mm thick), fix one end of the sample in the lower fixture of the universal testing machine, and pass the other end through a 5-0 surgical suture, with the lead-in point about 2mm from the upper end of the sample. Test related parameter settings: gauge length is 35mm, tensile speed is 15mm / min, and the maximum force when the sample breaks is its suture strength.
[0056] i. In vitro cell compatibility: All samples were cut into discs of uniform thickness and 16 mm in diameter. After the materials were sterilized, the cell compatibility of the materials was evaluated by the extract cell culture method and the cell material co-culture method.
[0057] j. Rat subcutaneous embedding tissue compatibility: Animal experiments were conducted to deeply evaluate the biocompatibility of the material after 7 and 28 days of implantation into rats.
[0058] raw material:
[0059] Polyvinyl alcohol particles: polyvinyl alcohol 1750, degree of polymerization 1700, alcoholysis degree 50%, Sinopharm Group Reagent Co., Ltd.;
[0060] Komagataeibacterxylinus: (KomagataeibacterxylinusATCC 23770).
[0061] Example 1
[0062] (1) Komagataeibacterxylinus ATCC 23770 was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0063] (2) First, 16 g of polyvinyl alcohol (polyvinyl alcohol 1750, degree of polymerization 1700, degree of alcoholysis 50%, Sinopharm Group Reagent Co., Ltd.) particles were weighed and added to 100 mL of deionized water, dissolved in a 95°C magnetic stirring water bath for 2 h, and a 16% (w / v, g / mL) PVA aqueous solution was prepared. 30 g of bacterial cellulose precipitate and 2 g of polyethylene glycol octylphenyl ether (Anhui Zesheng Technology Co., Ltd.) solution were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material (16% Porous PVA / BNC, referred to as 16% PPB) was obtained by repeated shaking and rinsing for 2 days.
[0064] Example 2
[0065] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0066] (2) First, 16 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 16% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate was added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the polyvinyl alcohol / bacterial cellulose composite artificial auricle material (16% PVA / BNC, referred to as 16% PB) was obtained by repeated shaking and rinsing for 2 days.
[0067] Comparative Example 1
[0068] The liquid culture medium was inoculated with Bacillus oxykogata, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C. The membrane was repeatedly incubated and purified until the hydrogel was transparent. Finally, it was repeatedly rinsed with ultrapure water until the pH was neutral to obtain a bacterial nanocellulose membrane (BNC).
[0069] Comparative Example 2
[0070] First, 16 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 16% (w / v, g / mL) PVA aqueous solution. The polyvinyl alcohol solution was poured into a mold, placed in a -20°C refrigerator and frozen for 36 h, then thawed at room temperature, and freeze-thawed for 3 times to obtain a polyvinyl alcohol hydrogel material (16% PVA).
[0071] Comparative Example 3
[0072] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0073] (2) First, 8 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare an 8% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate was added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the polyvinyl alcohol / bacterial cellulose composite artificial auricle material (8% PVA / BNC, referred to as 8% PB) was obtained by repeated shaking and rinsing for 2 days.
[0074] Comparative Example 4
[0075] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0076] (2) First, 12 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 12% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate was added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the polyvinyl alcohol / bacterial cellulose composite artificial auricle material (12% PVA / BNC, referred to as 12% PB) was obtained by repeated shaking and rinsing for 2 days.
[0077] Comparative Example 5
[0078] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0079] (2) First, 20 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 20% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate was added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times, and finally repeatedly shaken and rinsed for 2 days to obtain a polyvinyl alcohol / bacterial cellulose composite artificial auricle material (20% PVA / BNC, referred to as 20% PB).
[0080] Comparative Example 6
[0081] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0082] (2) First, 16 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 16% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate was added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed twice, and finally repeatedly shaken and rinsed for 2 days to obtain a polyvinyl alcohol / bacterial cellulose composite artificial auricle material.
[0083] Example 3
[0084] (1) The purchased BNC was homogenized into a homogenate state by a homogenizer (10,000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10,000 rpm for 10 min to collect the bacterial cellulose precipitate.
[0085] (2) First, 16 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 16% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate was added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times, and finally repeatedly shaken and rinsed for 2 days to obtain a polyvinyl alcohol / bacterial cellulose composite artificial auricle material.
[0086] Example 4
[0087] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0088] (2) First, 16 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 16% (w / v, g / mL) PVA aqueous solution. 40 g of bacterial cellulose precipitate and 1 g of polyethylene glycol octylphenyl ether solution were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -80°C refrigerator for 24 h, then thawed at room temperature, and freeze-thawed for 4 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0089] Example 5
[0090] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0091] (2) First, 8 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare an 8% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate and 1 g of polyethylene glycol octylphenyl ether solution were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0092] Example 6
[0093] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0094] (2) First, 30 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 30% (w / v, g / mL) PVA aqueous solution. 20 g of bacterial cellulose precipitate and 3 g of polyethylene glycol octylphenyl ether solution were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 24 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0095] Example 7
[0096] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0097] (2) First, 16 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 16% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate and 2 g of sodium dodecyl sulfate powder were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0098] Example 8
[0099] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0100] (2) First, 12 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 12% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate and 3 g of sodium dodecyl sulfate powder were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0101] Example 9
[0102] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0103] (2) First, 5 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 5% (w / v, g / mL) PVA aqueous solution. 40 g of bacterial cellulose precipitate and 1 g of sodium dodecyl sulfate powder were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 48 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0104] Example 10
[0105] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0106] (2) First, 30 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 30% (w / v, g / mL) PVA aqueous solution. 10 g of bacterial cellulose precipitate and 2 g of sodium dodecyl sulfate powder were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0107] Embodiment 11
[0108] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0109] (2) First, 16 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 16% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate and 2 g of sodium dodecyl sulfate powder were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0110] Example 12
[0111] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0112] (2) First, 16 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 16% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate and 2 g of sodium dodecyl sulfate powder were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0113] Example 13
[0114] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0115] (2) First, 12 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 12% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate and 3 g of sodium dodecyl sulfate powder were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0116] Embodiment 14
[0117] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0118] (2) First, weigh 5 g of polyvinyl alcohol particles and add them to 100 mL of deionized water, dissolve them in a 95°C magnetic stirring water bath for 2 h, and prepare a 5% (w / v, g / mL) PVA aqueous solution. Add 40 g of bacterial cellulose precipitate and 1 g of sodium dodecyl sulfate powder to the polyvinyl alcohol solution, stir them thoroughly at 350 rpm for 15 min, pour them into a mold, freeze them in a -20°C refrigerator for 48 h, then thaw them at room temperature, cycle freeze-thaw for 3 times, and finally repeatedly shake and rinse for 2 days to obtain a porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material.
[0119] Embodiment 15
[0120] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0121] (2) First, 30 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 30% (w / v, g / mL) PVA aqueous solution. 10 g of bacterial cellulose precipitate and 2 g of sodium dodecyl sulfate powder were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0122] Example 16
[0123] (1) Bacillus oxykogata was inoculated into a liquid culture medium, placed in a 30°C incubator for static fermentation for 5 days, and the bacterial cellulose membrane was collected and immersed in a 1% (w / v, g / mL) NaOH solution in a constant temperature water bath at 80°C, and repeatedly incubated and purified until the hydrogel was transparent, and finally rinsed repeatedly with ultrapure water until the pH was neutral. The BNC membrane was broken into a homogenate state by a homogenizer (10000 rpm, 15 min, 3 times), and then the bacterial cellulose homogenate was centrifuged at 10000 rpm for 10 min, and the bacterial cellulose precipitate was collected.
[0124] (2) First, 16 g of polyvinyl alcohol particles were weighed and added to 100 mL of deionized water, and dissolved in a 95°C magnetic stirring water bath for 2 h to prepare a 16% (w / v, g / mL) PVA aqueous solution. 30 g of bacterial cellulose precipitate and 2 g of sodium dodecyl sulfate powder were added to the polyvinyl alcohol solution, stirred at 350 rpm for 15 min, poured into a mold, and placed in a -20°C refrigerator for 36 h, then thawed at room temperature, and freeze-thawed for 3 times. Finally, the porous polyvinyl alcohol / bacterial cellulose composite artificial auricle material was obtained by repeated shaking and rinsing for 2 days.
[0125] The polyvinyl alcohol / bacterial cellulose artificial auricle material prepared in the example and the bacterial cellulose film, polyvinyl alcohol hydrogel and polyvinyl alcohol / bacterial cellulose material prepared in the comparative example were subjected to morphological observation, physical and chemical structure analysis, water test, mechanical property and biocompatibility test, etc. Figure 1 (Example 2, Comparative Examples 3, 4, 5, 6) It can be seen that within the polyvinyl alcohol concentration range of 8-20% (w / v, g / mL), as the polyvinyl alcohol concentration increases and the number of freeze cycles increases, the compressive strength and modulus of the polyvinyl alcohol / bacterial cellulose composite material are simultaneously enhanced. When 16% PB is freeze-thawed for 3 times, the compressive strength and modulus are as high as 4.11±0.44MPa and 10.62±0.30MPa, respectively. Figure 2(Examples 1, 2, Comparative Examples 1, 2) It can be seen that the porous polyvinyl alcohol / bacterial cellulose composite material (PPB) has visible holes on the surface, and the microscopic pore size is significantly increased to more than 10 microns, providing a more suitable space for cell and tissue growth. It can be seen from Table 1 (Examples 1, 2, Comparative Examples 1, 2) that the porosity of the 16% PPB material is 73.38%, which is further increased than that of the 16% PB, indicating that the pores are successfully made. Figure 3 (Examples 1, 2, Comparative Examples 1, 2) It can be seen that the prepared 16% PPB material has a wavelength of 3347 cm -1 、1161cm -1 and 1057cm- 1 The stretching vibration peaks of OH, cellulose glycosidic bond and CO, and PVA at 1562cm -1 and 2937cm- 1 The -CH2 bending and stretching vibration peaks at 100 nm indicate the successful preparation of the composite material. Figure 4 (Examples 1, 2, Comparative Examples 1, 2) It can be seen that the water content and saturated swelling ratio of 16% PPB are 89.37±0.24% and 402.67±21.35%, respectively, providing a suitable growth environment for cells. Figure 5 (Example 1) It can be seen that the 16% PPB material has excellent compressive mechanical properties, and its compressive strength and modulus are 3.69±0.12MPa and 9.67±0.79MPa respectively. The rigid fiber gives it strong compressive resistance. The cyclic compression test shows excellent elasticity, toughness and self-recovery, which fully meets the biomechanical requirements of the human auricle. Figure 6 (Examples 1, 2, Comparative Examples 1, 2) It can be seen that the 16% PPB material has excellent tensile mechanical properties, with tensile strength and modulus of 0.83±0.08MPa and 1.02±0.12MPa respectively, and elongation at break of 156.75±14.17%. PVA gives it excellent elasticity and can resist large tensile deformation. Figure 7 (Examples 1, 2, Comparative Examples 1, 2) It can be seen that the suture strength of the 16% PPB material is as high as 6.41±0.14N, which fully meets the requirements of clinical surgery. Figure 8 (Examples 1, 2, Comparative Examples 1, 2) It can be seen that the 16% PPB material has good cell compatibility, and its porous structure can support the growth of cells inward and cause cell aggregation. Fig. 9 and 10(Examples 1, 2, Comparative Examples 1, 2) It can be seen that the 16% PPB material can be well integrated with the host tissue, and the new cells, tissues and collagen fibers can completely wrap the material and migrate and grow inward, with good biocompatibility. However, the structure of 16% PB cannot support the inward growth of cells, so PPB obtains an internal structure that can support cell growth through surfactant foaming and pore making.
[0126] It can be seen from the above results that the present invention can effectively regulate the fiber network structure and mechanical properties of polyvinyl alcohol / bacterial cellulose composite materials. The prepared polyvinyl alcohol / bacterial cellulose porous composite materials have excellent mechanical strength, unique network pore structure and good biocompatibility. This invention is helpful to expand the development and application of polyvinyl alcohol and bacterial cellulose in the field of artificial organs and plastic repair prosthesis materials.
[0127] Table 1 Density, porosity and specific surface area of samples
[0128]
[0129] Table 2 Crystallinity of samples
[0130] sample Crystallinity / % BNC (Comparative Example 1) 44.73±5.07 16% PVA (Comparative Example 2) 35.80±8.60 16% PB (Example 2) 45.68±3.94 16% PPB (Example 1) 40.67±5.63
Claims
1. A prosthetic material, characterized in that: The prosthetic material is obtained by foaming raw materials containing bacterial cellulose and polypropylene alcohol under surfactant conditions and combining the freeze-thaw method.
2. A method for preparing a prosthetic material, comprising: (1) homogenizing bacterial cellulose and centrifuging to obtain bacterial cellulose precipitate; (2) mixing the polyvinyl alcohol aqueous solution, bacterial cellulose precipitate, and surfactant, stirring, freeze-thaw treatment, and washing to obtain a prosthetic material; Alternatively, the polyvinyl alcohol aqueous solution and bacterial cellulose are precipitated, mixed, stirred, freeze-thawed, and washed to obtain the prosthetic material.
3. The preparation method according to claim 2, characterized in that: The bacterial cellulose in step (1) is purified bacterial cellulose.
4. The preparation method according to claim 2, characterized in that: The homogenization parameters in step (1) are: 8000-12000 rpm, 15-30 min, 3-5 times; the centrifugation is 5000-11000 rpm for 5-10 min.
5. The preparation method according to claim 2, characterized in that: The concentration of the polyvinyl alcohol aqueous solution in step (2) is 5-30% (w / v); the degree of polymerization of the polyvinyl alcohol is 400-2500, and the degree of alcoholysis is 50-99%; The polyvinyl alcohol aqueous solution is prepared by mixing polyvinyl alcohol and water and dissolving them at 90-100° C. to obtain the polyvinyl alcohol aqueous solution.
6. The preparation method according to claim 2, characterized in that: In step (2), the content of bacterial cellulose precipitation in the mixed system is 10-40% (w / v); the content of the surfactant is 0-3% (w / v).
7. The preparation method according to claim 2, characterized in that: In the step (2), the surfactant is one or more of polyethylene glycol octylphenyl ether, sodium dodecyl sulfonate, sodium dodecyl sulfate, and fatty acids.
8. The preparation method according to claim 2, characterized in that: The freeze-thaw treatment in step (2) is as follows: thawing followed by freezing, wherein the freezing temperature is -80°C to -20°C for 12-48 hours; the thawing temperature is -4°C to room temperature for 8-12 hours; and the freeze-thaw treatment is cycled 1-5 times.
9. The preparation method according to claim 2, characterized in that: In the step (2), the stirring is performed at 300-350 rpm for 5-15 min; and the washing is performed by shaking washing for 1-2 d.
10. Use of the prosthetic material according to claim 1 in the field of cosmetic repair prosthetic materials for artificial auricle, cartilage, artificial skin, leather, chest, nose wing, and mandible.
